ADAPTA: A pilot randomised controlled trial of an alcohol-focused intervention versus a healthy living intervention for problem drinkers identified in a general hospital setting. (1st September 2015) - Watson, Judith M.; Fairhurst, Caroline; Li, Jinshuo; Tober, Gillian; Crosby, Helen; Lloyd, Charlie; Godfrey, Christine; Mdege, Noreen D.; Dale, Veronica; Toner, Paul; Parrott, Steve; Raistrick, Duncan; et al.
Highlights: No evidence of a difference in AUDIT score was seen between treatments at 6 months. A greater proportion in the healthy living group attended all 4 treatment sessions. Recruitment and follow up proved challenging with this non-help seeking group. Further thought needed regarding engaging problem drinkers in a hospital setting. Abstract: Aim: To examine the relative feasibility, acceptability, applicability, effectiveness and explore cost-effectiveness of a healthy living focused intervention (HL) compared to an alcohol-focused intervention (AF) for problem drinkers identified in hospital. Methods: A pragmatic, randomised, controlled, open pilot trial. Feasibility and acceptability were measured by recruitment, attrition, follow-up rates and number of treatment sessions attended. Effectiveness was measured using the Alcohol Use Disorders Identification Test score at six months. Additional economic and secondary outcome measures were collected. Results: Eighty-six participants were randomised and 72% ( n  = 62) were retained in full participation. Forty-one participants attended at least one treatment session (48%). A greater proportion in the HL group attended all four treatment sessions (33% vs 19%). Follow-up rates were 29% at six months and 22% at twelve months. There was no evidence of a difference in AUDIT score between treatment groups at six months. Mean cost of health care and social services, policing and the criminal justice system use decreased while EQ-5D scores indicated minor improvement in both arms. However, this pilot trial was not powered to detect differences in either measure between groups. Conclusions: While no treatment effect was observed, this study demonstrated a potential to engage patients drinking at harmful or dependent levels in a healthy living intervention. However, recruitment proved challenging and follow-up rates were poor. Better ways need to be found to help these patients recognise the harms associated with their drinking and overcome the evident barriers to their engagement with specialist treatment.